2021
DOI: 10.24875/ric.20000208
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sublingual and Intramuscular Administration of Vitamin B12 for the Treatment of Vitamin B12 Deficiency in Children

Abstract: Background: In most countries, contrary to some disadvantages, such as pain, relatively higher cost, and poor adherence to treatment, intramuscular (IM) route is still the primary treatment method for Vitamin B12 (VB12) deficiency. In recent years, because of these difficulties, new treatment methods are being sought for VB12 deficiency. Objectives: We aimed to compare sublingual (SL) and IM routes of VB12 administration in children with VB12 deficiency and to compare the efficacy of methylcobalamin and cyanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“… Tuğba-Kartal and Çağla-Mutlu (2020) also demonstrated in a retrospective review of 129 paediatric patients that a treatment regimen of sublingual B12 (both CN-Cbl and methyl-Cbl) at 1 mg once daily for 7 days then every other day for 3 weeks was as effective as the same dose schedule of IM B12 at normalising serum B12 levels. Finally, a recent 2021 study performed in a paediatric population (0–3 years) in Turkey found that a sublingual methyl-Cbl treatment regimen, comprising 1 mg daily replacement for a week followed by every other day for 2 weeks, 2 days/week for 2 weeks and once a week for 3 months was as effective as similar dose schedules of IM and oral CN-Cbl at normalising B12 levels ( Orhan Kiliç et al, 2021 ).…”
Section: Introductionmentioning
confidence: 95%
“… Tuğba-Kartal and Çağla-Mutlu (2020) also demonstrated in a retrospective review of 129 paediatric patients that a treatment regimen of sublingual B12 (both CN-Cbl and methyl-Cbl) at 1 mg once daily for 7 days then every other day for 3 weeks was as effective as the same dose schedule of IM B12 at normalising serum B12 levels. Finally, a recent 2021 study performed in a paediatric population (0–3 years) in Turkey found that a sublingual methyl-Cbl treatment regimen, comprising 1 mg daily replacement for a week followed by every other day for 2 weeks, 2 days/week for 2 weeks and once a week for 3 months was as effective as similar dose schedules of IM and oral CN-Cbl at normalising B12 levels ( Orhan Kiliç et al, 2021 ).…”
Section: Introductionmentioning
confidence: 95%
“…Replacement via IM is the most traditional choice for treating vitamin B 12 deficiency, in cases of inadequate dietary intake, pernicious anemia, gastrectomy, ileal resection or other malabsorption syndrome [68]. Its advantages are the effectiveness of the dose and the fact that it does not undergo changes in the effect of passing through the intestinal absorptive pathways.…”
Section: Vol 16 Iss 1 Year 2023 International Journal Of Nutrologymentioning
confidence: 99%
“…In addition to intramuscular and oral vitamin B 12 administration, new routes, such as sublingual and nasal administration, have recently become available. In addition to the obvious advantages over the oral and intramuscular routes (patient convenience and good adherence, safety, cost-effectiveness), sublingual and nasal treatments also provide a promising alternative for specific populations (infants, children, and the elderly) and patients with some specific conditions (swallowing disorders or malabsorption due to intestinal surgery, inflammatory intestinal diseases, or short bowel syndrome), for which oral and intramuscular routes are less appropriate [60,63,76,77]. Their efficacy has been extensively evaluated in recent years and has been demonstrated to be comparable to those of oral or intramuscular vitamin B 12 administration.…”
Section: Different Routes Of Vitamin B 12 Applicationmentioning
confidence: 99%